2017
DOI: 10.1097/md.0000000000005989
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke alterations in heart rate variability during orthostatic challenge

Abstract: Older adults following recovery from ischemic stroke have a higher incidence of orthostatic hypotension, syncope, and fall risk, which may be related to impaired autonomic responses limiting the ability to maintain cerebral blood flow. Thus, we investigated cerebrovascular and cardiovascular regulation in 23 adults ≥55 years of age, 10 diagnosed with ischemic stroke, and 13 age-matched healthy controls when sitting at rest and upon standing to compare differences of autonomic variables at ∼7 months (218 ± 41 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 30 publications
(59 reference statements)
1
28
0
1
Order By: Relevance
“…Recently, Rodriguez et al ( 2017 ) reported that there is no difference in spontaneous baroreflex sensitivity between stroke patients and healthy controls during standing up from a sitting posture. However, the gain values from SBP to EMG impulse were attenuated in patients, which suggests a post-stroke impairment of muscle-pump and baroreflex.…”
Section: Orthostatic Challenge and Orthostatic Intolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Rodriguez et al ( 2017 ) reported that there is no difference in spontaneous baroreflex sensitivity between stroke patients and healthy controls during standing up from a sitting posture. However, the gain values from SBP to EMG impulse were attenuated in patients, which suggests a post-stroke impairment of muscle-pump and baroreflex.…”
Section: Orthostatic Challenge and Orthostatic Intolerancementioning
confidence: 99%
“…We are only aware of one study that has investigated in older persons the post-stroke relationship in heart rate variability (HRV; Rodriguez et al, 2017 ) at rest and during changes in posture. A greater magnitude of decrease in LF HRV modulation upon standing up for the stroke group—indicating a transition to less sympathetic modulation—on average compared to the control subjects was observed.…”
Section: Orthostatic Challenge and Orthostatic Intolerancementioning
confidence: 99%
“…Another limitation is the lack of a protocol for challenging the autonomic nervous system. Rodriguez et al 31 evaluated alterations in HRV during orthostatic challenge at approximately 7 months post-stroke and found that the LF component of HRV when moving from a seated to a standing position was lower in the stroke group than in the control group, suggesting that cardiovascular autonomic dysfunction persists after recovery from stroke and that the cardiovascular response to standing may be impaired in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The selection criteria and the number of participants required to show statistical significance were based on previously published studies regarding hemodynamic responses to orthostatic loading (sit-to-stand test) in patients with stroke [7,10,28,31]. It was estimated that using a sample size calculator with an error probability (a) of 0.05, power (1-β) of 0.80 and an average effect size (d) of 0.5, the number of participants needed to achieve statistical significance was 37.…”
Section: Sample Size Calculationmentioning
confidence: 99%